Recent divergences and size decreases of eastern gorilla populations - Roy, Justin (Biol Lett, 2014)
Compared with other African apes, eastern gorillas (Gorilla beringei) have been little studied genetically. We used analysis of autosomal DNA genotypes obtained from non-invasively collected faecal samples to estimate the evolutionary histories of the two extant mountain gorilla populations and the closely related eastern lowland gorillas. Our results suggest that eastern lowland gorillas and mountain gorillas split beginning some 10 000 years ago, followed 5000 years ago by the split of the two mountain gorilla populations of Bwindi Impenetrable National Park and the Virungas Massif. All three populations have decreased in effective population size, with particularly substantial 10-fold decreases for the mountain gorillas. These dynamics probably reflect responses to habitat changes resulting from climate fluctuations over the past 20 000 years as well as increasing human influence in this densely populated region in the last several thousand years.